# Calculate the solution to these simultaneous equations using the elimination method: (1)(1)4𝑒+𝑓4e+f==44 (2)(2)𝑒−𝑓e−f==66

## Question

## Solution 1

The given equations are:

(1) 4e + f = 4 (2) e - f = 6

Step 1: Align the equations so that like terms are vertically aligned:

4e + f = 4 e - f = 6

Step 2: Add the two equations together. This will eliminate one of the variables:

(4e + e) + (f - f) = (4 + 6) 5e = 10

Step 3: Solve for e:

e = 10 Knowee AI is a powerful AI-powered study tool designed to help you to solve study problem.

```
Knowee AI is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI is a powerful AI-powered study tool designed to help you to solve study problem.
Knowee AI
```

## Similar Questions

Calculate the solution to these simultaneous equations using the elimination method: (1)(1)4𝑒+𝑓4e+f==44 (2)(2)𝑒−𝑓e−f==66

Calculate the solution to these simultaneous equations using the substitution method: (1)(1)𝑒+𝑓e+f==1010 (2)(2)4𝑒−5𝑓4e−5f==−14−14

Calculate the solution to these simultaneous equations using the elimination method: (1)(1)3𝑔+ℎ3g+h==44 (2)(2)𝑔−ℎg−h==44

Calculate the solution to these simultaneous equations using the elimination method: (1)(1)5𝑚+𝑛5m+n==1212 (2)(2)𝑚−𝑛m−n==66

Calculate the solution to these simultaneous equations using the elimination method: (1)(1)2𝑥+𝑦2x+y==00 (2)(2)𝑥−𝑦x−y==66

## Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.